The Effect of Brand Equity Dimension on Instant Noodle Purchase Decisions in Padang: Pengaruh Dimensi Ekuitas Merek terhadap Keputusan Pembelian Mie Instan Sedaap Cup di Padang - Eliza; Jumiatul Mulya (Perkumpulan Doktor Indonesia Maju, 2020)
The purpose of this study was to determine and analyze the effect of brand equity dimensions on the purchasing decision of Mie Sedaap Cup in Padang. Sampling in this study was conducted by purposive sampling. The sampling technique used is judgmental sampling. The sample in this study were 130 people. Data was collected in the form of questionnaires and analyzed through SPSS software ver. 24.0. The results in this study indicate that the Brand Equity Dimension has a positive and significant effect on Purchasing Decisions because the significance value of 0.052 <alpha 0.10 for Brand Awareness with a t-test value of 1.963> t-table of 1.6604, while the Quality Perception has a value significance of 0.001> 0.10 and t-test value 3.257> t-table 1.6604. This means that Brand Awareness and Quality Perception have a very strong influence on Purchasing Decisions separately (respectively). Furthermore, the magnitude of the effect of variance in brand equity dimensions on the purchasing decision of Mie Sedaap Cup was 52.3%. Based on the results of this study, it can be concluded that the Mie Sedaap Cup in its memory or memory usage is a good brand image by prioritizing product quality and purchasing decisions of the Mie Sedaap Cup.